2019
DOI: 10.3390/jcm8122187
|View full text |Cite
|
Sign up to set email alerts
|

Renal Tubular TRPA1 as a Risk Factor for Recovery of Renal Function from Acute Tubular Necrosis

Abstract: Background: Transient receptor potential ankyrin 1 (TRPA1), a redox-sensing Ca2+-influx channel, serves as a gatekeeper for inflammation. However, the role of TRPA1 in kidney injury remains elusive. Methods: The retrospective cohort study recruited 46 adult patients with acute kidney injury (AKI) and biopsy-proven acute tubular necrosis (ATN) and followed them up for more than three months. The subjects were divided into high- and low-renal-tubular-TRPA1-expression groups for the comparison of the total recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…CKF including renal tubular cell damage and death is the most common cause of CKD in hospitalized patients. 39,40 Studies using rat models of CKF have shown that adenine hemisulfate solution significantly increases BUN, serum creatinine, glomerular damage, tubular necrosis, interstitial fibrosis, and inflammatory mediators. 35,41,42 In addition, many inflammatory markers such as IL-1b, IL-6, IL-18, IL-33, and TNF-a increase during the progression of CKF.…”
Section: Discussionmentioning
confidence: 99%
“…CKF including renal tubular cell damage and death is the most common cause of CKD in hospitalized patients. 39,40 Studies using rat models of CKF have shown that adenine hemisulfate solution significantly increases BUN, serum creatinine, glomerular damage, tubular necrosis, interstitial fibrosis, and inflammatory mediators. 35,41,42 In addition, many inflammatory markers such as IL-1b, IL-6, IL-18, IL-33, and TNF-a increase during the progression of CKF.…”
Section: Discussionmentioning
confidence: 99%
“…In whole animals/humans, the role of TRPA1 in kidney disease remains unresolved. In a retrospective study, TRPA1 was upregulated in the renal tubules of patients with acute tubular necrosis and independently associated with failure to recover renal function 63 . Renal ischemia‐reperfusion injury (IRI) increased tubular TRPA1 expression in mice 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the management of CKD, this syndrome continues to be associated with unacceptable levels of morbidity and mortality [ 125 ]. A clinical observational study revealed that TRPA1 is upregulated in the renal tubules of patients with acute kidney injury (AKI) [ 126 ], leading study authors to suggest that TRPA1 is associated with the progression of AKI to CKD. Methylglyoxal, a reactive glucose metabolite, is elevated in CKD [ 127 ] and may be a central contributor to the inflammatory, structural, metabolic, and hemodynamic pathology of CKD [ 128 ].…”
Section: Trpa1 Channels and Vascular Diseasementioning
confidence: 99%